2021
DOI: 10.1007/s00198-020-05804-3
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral fracture: epidemiology, impact and use of DXA vertebral fracture assessment in fracture liaison services

Abstract: Summary Vertebral fractures are independent risk factors for vertebral and nonvertebral fractures. Since vertebral fractures are often missed, the relatively new introduction of vertebral fracture assessment (VFA) for imaging of the lateral spine during DXA-measurement of the spine and hips may contribute to detect vertebral fractures. We advocate performing a VFA in all patients with a recent fracture visiting a fracture liaison service (FLS). Fracture liaison services (FLS) are important service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 130 publications
(181 reference statements)
0
36
0
4
Order By: Relevance
“…Short et al [33] found that only the diagnosis of osteoporosis was associated with fractures in HIV-infected men, whereas other parameters, including hypogonadism, were not. However, they considered only self-reported fractures, and did not perform morphometric analysis, which may lead to underdiagnosis, being 65-75% of fragility fractures clinically "silent" [43]. Moreover, they used radioimmunoassay to determine free testosterone, which is unreliable [5].…”
Section: Discussionmentioning
confidence: 99%
“…Short et al [33] found that only the diagnosis of osteoporosis was associated with fractures in HIV-infected men, whereas other parameters, including hypogonadism, were not. However, they considered only self-reported fractures, and did not perform morphometric analysis, which may lead to underdiagnosis, being 65-75% of fragility fractures clinically "silent" [43]. Moreover, they used radioimmunoassay to determine free testosterone, which is unreliable [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth highlighting that a dual-energy X-ray absorptiometry (DXA) scan for BMD measurement is required in the majority of cases for a fracture risk assessment. As glucocorticoids are particularly associated with osteoporosis of trabecular bone, vertebral fracture assessment (VFA) should be included routinely when DXA scans are performed ( 145 ).…”
Section: Bone Preserving Treatments In Vasculitis: the Role Of Steroi...mentioning
confidence: 99%
“…Vertebral fracture assessment is a tool available on modern DXA machines and has proven the ability to detect vertebral fractures during the regular DXA-BMD measurement. 58…”
Section: Diagnosismentioning
confidence: 99%
“…Vertebral fracture assessment is a tool available on modern DXA machines and has proven the ability to detect vertebral fractures during the regular DXA-BMD measurement. 58 Trabecular bone score (TBS) is a noninvasive tool to assess bone microarchitecture from captured lumbar DXA images. 59 Thus, it might be considered as a measurement of bone quality.…”
Section: Diagnosis Dual-energy X-ray Absorptiometry and Trabecular Bo...mentioning
confidence: 99%